Combination effectiveness of glucomannan and moringa oleifera leaf extract on lipid profil of hypercholesterolemia rats - Wati, Dini Prastyo; Setyaningsih, Endang (Universitas Gadjah Mada, 2023)
cholesterol levels in the blood. This study aims to determine the effectiveness of the combination of glucomannan (Amorphophallus muelleri Blume) and Moringa oleifera leaf extract on the lipid profile of hypercholesterolemic Wistar rats. This research design used True experimental with a pretest-posttest control group design. The animal used in this study was 24 male Wistar rats (Rattus norvegicus) aged 8 weeks divided into 2 control groups and 6 treatment groups of glucomannan and Moringa oleifera leaf extract. The results of this study showed that there were significant changes in TC, TG, LDL-C, and HDL-C levels (p<0.05). It can be concluded that the combination of glucomannan (Amorphophallus muelleri Blume) and Moringa oleifera leaf extract can change the lipid profile effectively in the P5 (80mg/kgBW GAmB: 120mg/kgBW MoEL) and P4 (120mg/kgBW GAmB:80mg/kgBW MoEL ) as the most influential group in reducing TG, TC, LDL-C levels and increasing HDL-C levels.